RTS,S malaria vaccine pilot studies: addressing the human realities in large-scale clinical trials - Machteld van den Berg (Trials, 2019)
Abstract A malaria vaccine as part of the integrated malaria control and elimination efforts will have a major impact on public health in sub-Sahara Africa. The first malaria vaccine, RTS,S, now enters pilot implementation in three African countries. These pilot implementation studies are being initiated in Kenya, Malawi, and Ghana to inform the broader roll-out recommendation. Based on the malaria vaccine clinical trial experiences, key ethical practices for effective clinical trial research in low-resource settings are described. For successful vaccine integration into malaria intervention programs, the relational dynamics between researchers and trial communities must be made explicit. Incorporating community values and returning to research practices that serve the intended benefactors are key strategies that address the human realities in large-scale clinical trials and pilot implementation, leading to positive public health outcomes.